2018
DOI: 10.1146/annurev-lawsocsci-101317-031036
|View full text |Cite
|
Sign up to set email alerts
|

Violent Video Games, Sexist Video Games, and the Law: Why Can't We Find Effects?

Abstract: During the early 2000s, several states and municipalities sought to regulate minors’ access to violent video games owing to perceived harms to minors. The resultant case law, culminating in the US Supreme Court case Brown v. EMA (2011), demonstrated court skepticism of the science linking violent games to harm in minors. Such skepticism was increasingly confirmed as numerous newer studies could not link violent games to socially relevant outcomes. In more recent years, there has been a newer focus on sexist ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…However, scientific debates and press about whether the behavior infringing social norms in the virtual world will influence the behavior of off-line is becoming more and more active since 2000. And the degree of agreement between researchers is very low: only approximately 10-39.5% [12]. The work [13, p. 33] indicates that "the observation of the effect video game violence rather speculative and hypothetical than being built on a solid base of scientific evidence".…”
Section: Resultsmentioning
confidence: 99%
“…However, scientific debates and press about whether the behavior infringing social norms in the virtual world will influence the behavior of off-line is becoming more and more active since 2000. And the degree of agreement between researchers is very low: only approximately 10-39.5% [12]. The work [13, p. 33] indicates that "the observation of the effect video game violence rather speculative and hypothetical than being built on a solid base of scientific evidence".…”
Section: Resultsmentioning
confidence: 99%
“…The debate about videogames and the freedom of expression has been grounded in understanding videogames as a representational medium. As previously mentioned, the US Supreme Court concluded in 2011 that games are to be understood as a cultural expressive form that holds full protection rights as a medium of expression (Ferguson 2018, 61; Hakimi 2019, 2–3). While the interactive properties of games were acknowledged, the court concluded that interaction simply is to be understood as a more intense form of involvement compared to traditional media, and that videogames for this reason are not in essence different from other media of representation (Hakimi 2019, 2; Petersen 2014, 171).…”
Section: Understanding Videogames and The Freedom Of Expressionmentioning
confidence: 99%
“…Viewed as the most recent advancement on an evolutionary cultural timeline of representational media, we can start the discussion of videogames as an expressive medium by addressing the arguments used for judging other artistic expressions such as visual art, literature, and film (Hakimi 2019, 7). While research has not been able to determine that violent game representations are in themselves directly harmful (Elson & Ferguson 2014; Ferguson 2018), game scholar Marcus Schulzke argues that games that incite violence or deliver threats indeed may have the potential to cause psychological harm. An example is the first-person shooter game Ethnic Cleansing (Resistance Records 2002), in which players take the role of white supremacists violently attacking minority groups.…”
Section: Videogames As a Representational Mediummentioning
confidence: 99%
“…Many studies show that video games can be very helpful in education across different age groups and comprehension levels [44,35,2,32,27]. However, Others point out that video games can cause many problems in terms of health, time wasting, and, even, violence crimes [3,17,20].…”
Section: Introductionmentioning
confidence: 99%